2006
DOI: 10.1007/s10554-006-9116-5
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Origin of the Right Vertebral Artery from the Ascending Aorta in the Presence of an Aberrant Right Subclavian Artery

Abstract: We present a case of a 63-year-old man who was admitted to the hospital due to an acute coronary syndrome. Angiographic and magnetic resonance angiography examination showed an abnormal right vertebral artery originating from the ascending aorta, just above the left coronary sinus Valsalva in addition to aberrant retro-esophageal right subclavian artery. The variations and the incidence of various abnormal origins of the right vertebral artery are also reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…With respect to the vertebral artery, the left one has been reported to show anomalous origin at a frequency of 2.4–5.9 % in several large autopsy series (Lemke et al 1999; Akdeniz et al 2007; Ikegami et al 2007). However, an anomalous origin of the right vertebral artery has been reported to be rarer, being detected as a coincidental finding during surgery or at autopsy (Akdeniz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the vertebral artery, the left one has been reported to show anomalous origin at a frequency of 2.4–5.9 % in several large autopsy series (Lemke et al 1999; Akdeniz et al 2007; Ikegami et al 2007). However, an anomalous origin of the right vertebral artery has been reported to be rarer, being detected as a coincidental finding during surgery or at autopsy (Akdeniz et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the vertebral artery, the left one has been reported to show anomalous origin at a frequency of 2.4–5.9 % in several large autopsy series (Lemke et al 1999; Akdeniz et al 2007; Ikegami et al 2007). However, an anomalous origin of the right vertebral artery has been reported to be rarer, being detected as a coincidental finding during surgery or at autopsy (Akdeniz et al 2007). In fact, many of the reports describing anomalous origin of the right vertebral artery are coincidental findings during surgery (Palmer 1977; Rieger and Huber 1983; Chen et al 1998; Lemke et al 1999; Best and Bumpers 2002; Yanik et al 2004; Goray et al 2005; Akdeniz et al 2007; Ka-Tak et al 2007; Satti et al 2007; Kau et al 2008; Park et al 2008; Kim et al 2009), although such findings at autopsy have also been reported (Mori et al 1990; Gluncic et al 1999; Fazan et al 2004; Ikegami et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case each originated between the left common carotid artery and left subclavian artery and between the right subclavian artery and right common carotid artery (with lack of an innominate artery). Akdeniz et al 2 report the 10th case of an aberrant right VA arising from the proximal aortic arch just above the left coronary sinus, which is the sole description of a proximal/ascending aortic origin of an aberrant right VA.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Ano ma lo us ori gin of the ver teb ral ar tery is onlypre sentin15.7%ofca seswithaber rantright subc la vi anar tery. [11][12][13] Thecli ni calsig ni fi can ceof ano ma lo usver teb ralar teryori ginsisnotcle ar,yet inmostca sesdes cri bedintheli te ra tu re,ano ma lousver teb ralar teryori ginsdidnotre sultincli ni cal symptoms.The reareveryfewre portsdes cri bing pa ti entswhocomp la i nedofsymptomsofver tebro ba sil laryin suf fi ci ency.Kin kingofver teb ralarteryandin cre a sedin ci den ceofar te ri aldis sec ti on withano ma lo usori ginofthever teb ralar terywas al sore por ted.The o re ti cally,al te redhe mody na mics ca u setur bu len ce,whichmaypre dis po sethepa tientstoane urysms,andthe re fo rein cre a setherisk oface reb ro vas cu larac ci dent.Ho we ver,the reisno conc lu si veevi den cethatthe seva ri antsle adtoa pre dis po si ti ontoce reb ro vas cu lardi sor ders. 4,5 Alt ho ughsup ra a or ticvas cu larano ma li esare con si de redasana to micva ri ants,theyarepo ten tiallyim por tanttobere cog ni zedpri ortovas cu lar sur geryinthehe adandneckre gi on,aswellasduringtheaor ticarchsur gery.Thisisimportantin or dertoavo idac ci den talvas cu larin juryandop timi zeac cessforvas cu laranas to mo sisdu ringsurgery.De ta i ledknow led geofano ma lo usori ginof sup ra a or ticbranc hesisal soofim por tan ceforpa tientswhoaretoun der gofo ur-ves selce reb ralan giog raphy in an emer gency unit to ru le out, for examp le,thepos si bi lityofin trac ra ni alane urysm af tersu ba rach no idhe morr ha ge.Ifthever teb ralartery ori gin is unk nown, the pa ti ent might be wronglydi ag no sedasver teb ralar teryhypop la si a orap la si a.Thisle a vesthepro ba bi lityofmis singthe pat ho logy,suchasdis sec ti onorane urysmfor ma tioninthemis sedver teb ralar tery.Additionally,, know led ge of the va ri a ti ons in the aor tic arch branc hingpat ternbe co mesmo reim por tantinthe eraofca ro tidorver teb ralar terystentsandnew the ra pe u ticop ti onsforin ter cra ni alin ter ven ti ons.…”
Section: Dıs Cus Sı Onmentioning
confidence: 99%